2013
DOI: 10.1212/wnl.0b013e3182a6cb72
|View full text |Cite
|
Sign up to set email alerts
|

Interictal increase of CGRP levels in peripheral blood as a biomarker for chronic migraine

Abstract: Increased CGRP level measured in peripheral blood outside migraine attacks and in the absence of symptomatic medication could be a biomarker helping in the diagnosis of CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
331
10
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 381 publications
(380 citation statements)
references
References 32 publications
(39 reference statements)
29
331
10
10
Order By: Relevance
“…In chronic migraine, a recent study in patients shows high levels of CGRP in the peripheral blood (measured by ELISA) as well as also in the pain-free interval when compared with healthy controls [76], suggesting that CGRP measure might be a biomarker of CM.…”
Section: Migraine Pathophysiology: the Role Of Cgrpmentioning
confidence: 98%
“…In chronic migraine, a recent study in patients shows high levels of CGRP in the peripheral blood (measured by ELISA) as well as also in the pain-free interval when compared with healthy controls [76], suggesting that CGRP measure might be a biomarker of CM.…”
Section: Migraine Pathophysiology: the Role Of Cgrpmentioning
confidence: 98%
“…Nevertheless, with Oterino et al (2), levels of plasmatic CGRP in controls were lower, although differences were not significant, than in migraine patients. CGRP has recently been found to be a good marker for chronic migraine, but its interpretation is not trouble free (3).…”
Section: Dear Sirmentioning
confidence: 99%
“…6 Despite their wide uptake and recommendation as standard care for migraine attacks, triptans do not work for all patients and their use for migraine is relatively low in the United States. 5,7 In the longitudinal American Migraine Prevalence and Prevention (AMPP) study, 18.3% of respondents used triptans; only 21.7% of respondents who were taking triptans were using them as monotherapy, while the remainder combined triptans with nonsteroidal anti-inflammatory drugs (NSAIDs; 43.3%), over-the-counter (OTC) analgesics (34.1%), or other OTC medications (34.8%). 7 This study found that triptan use was associated with higher levels of disability related to headache and higher headache frequency.…”
Section: Introductionmentioning
confidence: 99%